Georgia : Poverty Update - World Bank (Washington, DC, 2013)
This povert y update finds the following: Between 1997 and 2000, poverty has increased unambiguously, for a full set of poverty lines and definitions of poverty measures. Poverty has increased because over the period, consumption fell and inequality rose. Living standards have not risen despite growth in Gross Domestic Product because growth was too weak, too concentrated in a narrow set of sectors, and there were no effective mechanisms to redistribute its benefits. The 1998-99 crisis hit those who were benefiting from the period of growth--the self-employed and private sector workers. But the worse impact of the crisis was on the most vulnerable, and particularly on children. the depth and severity of poverty have increased, and the most socially vulnerable have become poorer and more deprived. it is not clear what the government did to prevent the worsening of poverty; on the one hand, the government created adequate foundations for a market economy, enabling private sector growth, and on the other hand, the government did very litle to help the poor directly and in some key respects the situation was made worse by allowing the accumulation of arrears on pensions, salaries for teachers, and other social expenditures. The report further examines why government performance in implementing anti-poverty measures was inadequate; the signs that the situation is changing; key challenges for poverty reduction; and identifies priorities the government must address.